(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article discusses the role of adverbs in narrative text and the types of adverbs. The article also presents the opinions of various foreign scholars about adverbs and their functions. Examples are provided for each type of adverb and also analysis of adverbials are highlighted in this article.